Development of an online catalog of the Diliman Interactive Learning Center's collection based on learning object metadata - Surmieda, Janny S. (School of Library and Information Studies, University of the Philippines Diliman, 2008)
The main goal of the study was to create an online catalog for the collection for Diliman Interactive Learning Center (DILC) using Learning Object Metadata (LOM). Among its objectives were to enumerate the fields of LOM that would be able to describe the collection of DILC and to enumerate the functionality and features needed in the online catalog.